Risk Factors and Prognosis for Metastatic Cutaneous Squamous Cell Carcinoma: A Cohort Study - Jaakko S. Knuutila; Pilvi Riihilä; Samu Kurki; Liisa Nissinen; Veli-Matti Kähäri (Medical Journals Sweden, 2020)
Cutaneous squamous cell carcinoma (cSCC) has metastatic potential. The aims of this study were to identify the risk factors for metastasis of primary cSCC and for poor prognosis in metastatic cSCC. Retrospective primary tumour cohorts of metastatic cSCCs (n = 85) and non-metastatic cSCCs (n = 218) were analysed. The mean annual rate of metastasis for primary cSCCs was 2.28%. In 49.4% of patients with metastatic cSCC, metastasis was detected within 6 months of diagnosis of the primary cSCC. There was no prior history of cSCC in 84.7% of metastatic cSCCs. Risk factors for metastasis included Clark's level 5, tumour diameter 20-29.9 mm, age at diagnosis < 50 or 70-79 years, and location on lower lip or forehead. A reduced risk of metastasis correlated with: isosorbide mono-/di-nitrate and/or aspirin use; comorbidity with actinic keratosis or basal cell carcinoma; and actinic keratosis or cSCC in situ as part of, or confirmedly preceding, primary cSCC. Poor prognosis in metastatic cSCC correlated significantly with ≥3 nodal metastases and extranodal extension of metastasis. These results characterize new risk factors for metastatic cSCC.